2014
DOI: 10.1097/hmr.0b013e3182915e44
|View full text |Cite
|
Sign up to set email alerts
|

Executive compensation in health care

Abstract: To address critics who assert health care executive compensation levels are not consistent with organizational performance, health care organization CEOs, board members, and consultants would benefit to carefully consider and effectively communicate the numerous factors influencing executive compensation beyond firm financial performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…in readiness for possible OHS challenges (13). Enterprises should be willing to assist in medical treatment, carry out rehabilitation management (52), and provide compensation for employees (58) in the case of occupational diseases. Models and methods of comprehensive health management (59), employee participation management, electronic information intervention, OHS programs, and individualized health management will continue to be a focus for research.…”
Section: Ohsm Mode and Methodsmentioning
confidence: 99%
“…in readiness for possible OHS challenges (13). Enterprises should be willing to assist in medical treatment, carry out rehabilitation management (52), and provide compensation for employees (58) in the case of occupational diseases. Models and methods of comprehensive health management (59), employee participation management, electronic information intervention, OHS programs, and individualized health management will continue to be a focus for research.…”
Section: Ohsm Mode and Methodsmentioning
confidence: 99%
“…We controlled for hospital- and area-level characteristics consistent with previous studies that examined hospital CEO compensation (Shay & White, 2014). Hospital-level characteristics included number of beds (categorical), hospital–system affiliation, rural status, teaching status, religious affiliation, network affiliation, geographic region, whether contract managed, and profit margin (Young, Chou, Alexander, Lee, & Raver, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, there is little research in the academic literature examining whether this holds true for hospital CEOs. Instead, the existing literature on hospital CEO compensation focuses on other human capital characteristics, organizational characteristics, or organizational performance as important determinants of hospital CEO compensation (Santerre & Thomas, 1993; Shay & White, 2014; Joynt et al, 2014; Reiter, Sandoval, Brown, & Pink, 2009). Some of these studies include gender as a control in the analysis but not as the primary variable of interest (Brickley, Van Horn, & Wedig, 2010; Santerre & Thomas, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing executive compensation studies have consistently found a significant relationship between organization size and CEO pay, with a 10% increase in revenues leading to approximately 2% to 3% increase in compensation (Hallock, 2002;2011;Murphy, 2013). Moreover, the correlation between organization size and CEO compensation holds in hospital studies (Shay & White, 2014). We therefore adjust our estimates to account for organizational size.…”
Section: Accounting For Organization Sizementioning
confidence: 99%